How accretion of planet-forming disks influences stellar abundances - Hühn, León-Alexander; Bitsch, Bertram (Astronomy and astrophysics, 2023)
Millimeter-sized dust grains experience radial velocities exceeding the gas velocities by orders of magnitude. The viscous evolution of the accretion disk adds disk material onto the central star's convective envelope, influencing its elemental abundances, [X/H]. At the same time, the envelope mass shrinks as the stellar age increases, amplifying the rate of abundance change. Therefore, the elemental abundances of the star are sensitive to disk processes that alter the composition and timing of disk accretion. We performed numerical 1D log-radial simulations integrating the disk advection-diffusion equation, while accounting for evaporation and condensation of chemical species at the evaporation fronts. They reveal a peak of refractory abundance within the first 2 Myr of Δ[X/H] ~ 5 × 10−2 if grain growth is significant, but subsequent accretion diminishes previous refractory abundance increases for long-lived disks. Planet formation can reduce the abundance of dust species whose evaporation fronts lie within the planet's orbit by preventing solids from reaching the inner edge once the planet starts opening a gap exerting a pressure bump exterior to its orbit and consequently blocking inward drifting pebbles. We expect the accretion of the solar protoplanetary disk with Jupiter present to have changed the Sun's elemental abundances by ~1 × 10−2 throughout its lifetime. These considerations were also applied to the HD106515 wide binary system. We find that measurements of Δ[X/H] are in reasonable agreement with results from simulations where the observed giant planet around HD106515 A is included and if HD106515B's disk formed planetesimals more efficiently. Simulations where the planet formed inside the water ice line are more favorable to agree with observations. Even though the general changes in the stellar abundances due to disk accretion are small, they are detectable at current sensitivities, indicating that the methods presented here can be used to constrain the planet formation pathway.